Differential Immune Response against Recombinant Leishmania donovani Peroxidoxin 1 and Peroxidoxin 2 Proteins in BALB/c Mice - Nada S. Daifalla; Abebe Genetu Bayih; Lashitew Gedamu (Journal of Immunology Research)
We assessed the immune response against recombinant proteins of two related, albeit functionally different, peroxidoxins from Leishmania donovani: peroxidoxin 1 (LdPxn1) and peroxidoxin 2 (LdPxn2) in BALB/c mice. We also evaluated the effect of coadministration of TLR agonists (CpG ODN and GLA-SE) on the antigen-specific immune response. Immunization with recombinant LdPxn1 alone induced a predominantly Th2 type immune response that is associated with the production of high level of IgG1 and no IgG2a isotype while rLdPxn2 resulted in a mixed Th1/Th2 response characterized by the production of antigen-specific IgG2a in addition to IgG1 isotype. Antigen-stimulated spleen cells from mice that were immunized with rLdPxn1 produced low level of IL-10 and IL-4 and no IFN-γ, whereas cells from mice immunized with rLdPxn2 secreted high level of IFN-γ, low IL-4, and no IL-10. Coadministration of CpG ODN or GLA-SE with rLdPxn1 skewed the immune response towards a Th 1 type as indicated by robust production of IgG2a isotype. Furthermore, the presence of TLR agonists together with rLdPxn1 antigen enhanced the production of IFN-γ and to a lesser extent of IL-10. TLR agonists also enhanced a more polarized Th 1 type immune response against rLdPxn2.